A vibrational spectroscopic investigation on benzocaine molecule - Balcı, Kubilay; AKYÜZ, SEVİM (ELSEVIER SCIENCE BV, PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS, 2008)
The stable conformers of free benzocaine molecule in electronic ground state were searched by means of successive single point energy calculations carried out at B3LYP/3-21G level of theory. The obtained calculation results have indicated that the molecule has three different stable conformers (one trans and two gauche) at room temperature. The resultant equilibrium geometrical parameters of these stable conformers were determined through the geometry optimizations performed at B3LYP/6-31G(d), B3LYP/6-3l++G(d,p), B3LYP/aug-cc-pvTZ and MP2/6-31++G(d,p) levels of theory, separately. The vibrational normal modes of each conformer and associated wavenumbers, IR intensities and Raman activities were calculated in the harmonic oscillator approach at B3LYP/6-31G(d), B3LYP/6-3l++G(d,p), B3LYP/aug-cc-pvTZ levels of theory. In the fitting of the calculated harmonic wavenumbers to the experimental ones, two different scaling procedures, called "Scaled Quantum Mechanics Force Field (SQM FF) methodology" and "scaling wavenumbers with dual scale factors", were proceeded independently. Both procedures have yielded results in very good agreement with the experiment and thus proved the necessity of proceeding an efficient scaling procedure over the calculated harmonic wavenumbers for performing a correct vibrational spectroscopic analysis on the basis of B3LYP calculations. In the light of the obtained scaled theoretical spectral data, a successful assignment of the fundamental bands observed in the recorded IR and Raman spectra of the free molecule was achieved. (C) 2008 Elsevier B.V. All tights reserved.
Keywords: Benzocaine; Ethyl 4-aminobenzoate; Scaled frequencies; IR and Raman spectra; Vibrational modes; SQM (Scaled Quantum Mechanics); local-anesthetic drugs; cloned channel kv1.5; force-fields; crystal polymorphism; scaling factors; raman-spectra; dipole-moment; benzoic-acid; hartree-fock; in-vivo; Etil 4-aminobenzoat; ölçeklendirilmiş frekanslar; İR ve Raman spektrumları; titreşim modları; SQM (Ölçekli Kuantum Mekaniği); lokal anestetik ilaçlar; Klonlanmış kanal kv1.5; kuvvet alanları; kristal polimorfizmi; ölçekleme faktörleri; Raman spektrumları; Dipol momenti; benzoik asit